(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
The current study investigates the in-vivo hepatoprotective effectiveness of Bougainvillea glabra stem extract against alcohol and paracetamol-induced hepatotoxicity in animal models. The alterations in liver enzymes including serum glutamic oxaloacetic transaminase (SGOT), serum glutamic pyruvic transaminase (SGPT), alkaline phosphatase (ALP), and total bilirubin are studied in rats given B. glabra extract with paracetamol or alcohol to produce hepatotoxicity. The levels of glutathione and lipid peroxidation were also examined, and the outcomes were contrasted with silymarin as the reference. The acute toxicity studies presented the plant extract under category 5 of GHS system, which further motivated the studies for hepatoprotective activity. The induction of hepatotoxicity was confirmed with the elevated levels of serum and tissue biochemical by the administration of paracetamol and alcohol. Under paracetamol as a hepatotoxin, the animals with 200 and 400 mg/kg p.o demonstrated near figures for SGPT and SGOT of the group treated with silymarin with significance. The results were still more appreciative under alcohol as a hepatotoxin. In both cases, the group with 400 mg/kg p.o gave a promising result with the reduced inflammatory cells under histopathological studies.